Research on multiagent governance of the marine ecoeconomic system in China considering marine scientific research institutions and media - Gao, Lehua; Yan, Hongyi; Cai, Dongyang (Frontiers in Environmental Science, 2023)
The multiagent governance model of the marine ecoeconomic system requires local governments to actively guide the participation of social subjects. Under the new reality of multiagent governance mechanism, this study proposes an analytical framework for describing the dynamic relation between local governments and marine production enterprises. It uses the analytical tools of evolutionary game theory to establish an evolutionary game system between the two parties and takes China as the specific research object. For doing so, it selects marine scientific research institutions and media with a strong public value representation and discusses the unilateral evolutionary stability strategy of the system by introducing four parameters, namely, the number of marine scientific research institutions, the contribution level of marine scientific research institutions, the participation level of media, and the authenticity level of information released by media. Furthermore, we used MATLAB to simulate and analyze by combining our research data in 14 cities in coastal areas of China. The results demonstrate that: (1) improving the contribution level and number of marine scientific research institutions is conducive to the collaborative governance of the marine ecoeconomic system; (2) the authenticity level of information released by media is positively correlated with the development of the multiagent governance model of the marine ecoeconomic system; and (3) differently biased objects with distorted media report information affect the trend of the governance effect of the marine ecoeconomic system. Thus, a timely improvement or reduction of the participation level of media is necessary.